Investing in Shares of CSR Companies as an Instrument of Investment Risk Management - Olejnik, Paweł (Journal of Public Governance, 2024)
Objective: Corporate Social Responsibility (CSR) is a concept of running a company that is more and more implemented among companies around the world. Not only companies are more and more interested in CSR, but also the financial community. The objective of this study is to research the influence of CSR on the investment risk level among companies whose shares are listed on the Warsaw Stock Exchange. Research Design & Methods: In this study, an analysis and assessment of literature was used as well as empirical research whose scope covers the period of 2009–2017. In empirical research for investments in shares of companies included in the RESPECT Index there were estimated risk measures and their levels were compared with levels of those risk measures for investment in WIG. Findings: Companies from the RESPECT Index were characterised by higher total risk and lower systematic risk. Moreover, the results of skewness and kurtosis were mixed. Implications / Recommendations: The practical implication of this study is showing companies whose shares are listed on the Warsaw Stock Exchange and which implemented CSR. Moreover, mixed results of this study demonstrate that investing in shares of CSR companies is a complex issue, because the results depend on the kind of risk that is analysed. This is important knowledge in investment risk management. Information about companies that implemented CSR and about the risk level of those companies is important to investors who want to invest in CSR companies as well as to the managers of companies, because the influence of CSR on the investment risk level is indicated. Contribution / Value Added: Investing in CSR companies is a complex issue and its results depend on risk measure. The added value of this study is to compare risk levels for investment in shares of companies included in the RESPECT Index with risk levels for investment in WIG. Moreover, this study contributes to a better understanding of the consequences of implementing CSR in a company as well as better understanding of a company’s attractiveness for investors. Article classification: research article JEL classification: G32, M14